TALENT RETENTION IN GEN Z WORKFORCE: THE ROLE OF PURPOSES DRIVEN LEADERSHIP AND CAREER DEVELOPMENT OPPORTUNITIES - TH, Leonardus; Rosalia, Nirma (Penelitian dan Pengembangan Ilmu, 2025)
The conclusion of this study shows that purpose-driven leadership has a significant influence on the retention of Generation Z talent. Purpose-oriented leadership can provide greater meaning and relevance to Gen Z than traditional leadership styles. In addition, career development opportunities serve to strengthen this relationship by providing a clear and concrete growth path. This finding expands the study of generation-based human resource management, particularly by including purpose-driven leadership as a significant determinant in the retention of young employees. From a practical perspective, organizations are advised to combine purpose alignment with a structured career development strategy to minimize the turnover rate of Gen Z. Ultimately, the results of this study emphasize the urgency of building organizations that are not only progressive in providing career opportunities, but also meaningful in making contributions that align with the values ​​and aspirations of future generations.